METAPHORS IN SELENA GOMEZ’S SONG KILL ‘EM WITH KINDNESS: A SEMANTIC ANALYSIS - Feisy Mokoagouw; Nitha V. F. Liando; Tirza A. Kumayas (SoCul: International Journal of Research in Social Cultural Issues, 2022)
This research is descriptive qualitative research that analyzes the metaphors in the song lyric Kill 'Em With Kindness by Selena Gomez. The purposes of the study are to identify the types of metaphors and to find the theme of the lyrics in the song Kill 'Em With Kindness. The metaphor theory is used to categorize metaphorical expressions into several types. The findings show that there are 3 metaphorical expressions with 9 metaphors found within Gomez’s song. These metaphors are categorized into three types of metaphors: 3 nominal metaphors, 4 predicative metaphors, and 2 sentential metaphors. Predicative metaphors are the most common of the three types of metaphors. The song's theme is revealed by elaborating on the metaphorical meanings and shared concepts. From the shared concepts in some metaphorical expressions such as [+violence], [+painful], [+against], [-worthy], [+point], [+destroyed], [+quarrel], [+disgrace], [+anger] the probable theme that can be drawn is “nothing is better than kindness”. The theme is derived from an understanding of the song's overall plot as depicted by the lyrics. Overall, the lyrics depict a situation of how humans more concerned about commenting on other’s importance with cruelty, violence and bullying while the best way to treat people is through kindness. Finally, all the negativities are not ensured all the piece, just from kindness all the things will come good and peace itself.